Late Type 3b Endoleak with an Endurant Endograft - Mehmet Barburoglu; Bulent Acunas; Yilmaz Onal; Murat Ugurlucan; Omer Ali Sayin; Ufuk Alpagut (Case Reports in Radiology)
Endovascular stent grafting with different commercially available stent graft systems is widely applied for the treatment of abdominal aortic aneurysms with high success rates in the current era. Various types of endoleaks are potential complications of the procedure. They usually occur in the early period. In this report, we present type 3b endoleak occurring 14 months after a successful endovascular abdominal aortic aneurysm repair with a Medtronic Endurant stent graft.